Multiple Organ Dysfunction Reduces In-Hospital Survival in COVID-19 Patients - Abdulrazzaq, Najiba; Naeem, Kashif Bin; Alhajiri, Abdalla; Chkhis, Ayman; Choondal, Vinod; Osman, Mona; Almusa, Kusay (International Journal of Innovative Research in Medical Science, 2020)
Background: Although primarily a respiratory illness, COVID-19 involves multiple organs when the disease is severe or critical. Hence, we conducted this study to evaluate the incidence of multiple organ dysfunction in COVID-19 patients and its implications on survival. Methods: A retrospective analysis of laboratory-confirmed COVID-19 patients presenting to our center in Dubai, UAE between April 2020 and July 2020. Data was collected from the electronic medical records and analyzed to evaluate multiple organ damage observed during hospital admission. Findings: Five-hundred patients were studied. Overall mean age was 49.5 years (range 13-94), 76% males, 33% diabetics, 31% hypertensives. 97/500 (19.4%) had evidence of single organ damage; 37/500 (7.4%) had two organ damage; and 105/500 (21%) had more than two organ damage. Acute respiratory distress syndrome was the most prevalent organ damage,153/500 (30.6%); followed by acute cardiac injury, 120/500 (24%); acute kidney injury 107/500 (21.4%); acute liver injury 96/500 (19.2%); septic shock 93/500 (18.6%); disseminated intravascular coagulation 27/500 (5.4%), and heart failure 17/500 (3.4%). We found that in-hospital survival reduced as the number of organs involved increased; only 20% patients survived who had more than 2 organ damage. Also, the chances of survival reduced considerably once other organs were involved in addition to the acute respiratory distress syndrome (91.6% survival in ARDS alone vs. 28.6% survival in ARDS with acute kidney injury vs. 10.4% survival in ARDS with shock/acute cardiac injury/acute kidney injury). Conclusion: Multiple organ dysfunction is common in COVID-19 as 21% had evidence of more than two organ damage in our study. The survival in COVID-19 reduces significantly once multiple organs are involved. Early monitoring and recognition of multiple organ dysfunction is necessary to prevent adverse outcomes and improve survival.